IMPLEMENTASI APLIKASI MANAJEMEN SURAT (AMS) DALAM PROSEDUR PENGELOLAAN SURAT MASUK DAN SURAT KELUAR DI PT PLN (PERSERO) WILAYAH SUMATERA BARAT - Rita Permata Sari (Jurnal Ecogen, 2018)
The purpose of this study was to find out how the implementation of the Letter Management Application (AMS) in managing the incoming and outgoing mail at PT PLN (Persero) in the West Sumatra region as well as the obstacles faced in the management of incoming and outgoing mail electronically. This study uses descriptive qualitative research methods. Determination of informants in the study was carried out with purposive sampling technique that aims to get the information obtained more targeted because the information has been determined in advance. Data retrieval is done through observation, interviews and documentation, with Model Miles and Huberman data analysis techniques. The results showed that the implementation of AMS in the West Sumatra Regional Electric Company had been carried out well but it had not been run optimally. It was seen that there was still a long time to complete the incoming and outgoing letters, even though the process of entering the letter data into the Letter Management Application did not take a long time but the letter arrived at the hands of consumers. it still takes a long time, besides that there is a discrepancy between the implementation of the procedure of incoming and outgoing mail with the theory set, the lack of technical guidance or special training in handling incoming and outgoing mail using the Letter Management Application. Keyword:  Implementation, AMS, Management of Incoming Mail and Outgoing Mail